The Impact of Online Learning System on Students Affected with Stroke Disease. (7th February 2022) - Wassan, Sobia; Xi, Chen; Shen, Tian; Gulati, Kamal; Ibraheem, Kinza; Amir Latif Rajpoot, Rana M.
Abstract : Stroke, also known as a cerebrovascular accident, is a medical emergency that causes temporary or permanent behavioral dysfunction in people. Sleep deprivation affects our brains in a variety of ways. The advantages of sleep much justify the risks of not having enough sleep. Sleep deprivation (SD) includes a variety of factors, including prolonged awake. Neuroimaging investigates SD's impact on attention, working memory, mood, and hippocampal learning. We analyzed how this data enriches our mechanistic understanding of these alterations and the clinical illnesses linked with sleep disruption. We have used Cronbach's alpha to test the reliability of a scale, so we then have 19 individual attributes responding to 174 participants via survey. The evaluated result shows the reliability statistics; the value for Cronbach's alpha is .962, which is very excellent as it reaches 1. So, there is very strong reliability. If the value falls under .6, we look back to the mean and standard deviation table and remove the attribute with low values for mean or standard deviation and try the remaining attributes. Cronbach's alpha tells us which attribute or item to delete to increase the reliability, and we also have analyzed the correlation among the class students while watching the same video lecture. We have collected data for at least ten students watching the same video using a webcam. Once the data is collected, we then have applied some correlation techniques to determine the class students' behavior towards the same video lecture. This way, we can see the overall behavior of the class upon a specific video lecture. The study further reveals that subjective happiness is influenced by its efficiency, entertainment value, and effectiveness. Does the research offer an original emphasis on analyzing how does lack of sleep affect our brains? Sleep loss frameworks are minimal compared to the benefits of sleep.